UFIDA Software (China) Co. Ltd.-- A Case Study Of Serial Adjustments For A New Marketing Strategy - Nan, Wang (2008)
The conversion in marketing strategy is an important conversion in relation to company\'s long-term development. To adapt to change in marketing strategy, company always makes series of regulation on other coordinating policy.